Agroecologically-conducive policies: A review of recent advances and remaining challenges - Place, Frank; Niederle, P.; Sinclair, F.; Estrada-Carmona, Natalia; Guéneau, S.; Gitz, V.; Alpha, A.; Sabourin, E.; Hainzelin, E. (Transformative Partnership Platform on Agroecology, 2022)
The debate concerning the need for significant transformations towards more nutrition oriented, environmentally sustainable and inclusive food systems has generated increased attention towards agroecology in recent years. Literature on this subject has already demonstrated that transitions to agroecology will be context specific, as countries and regions have distinctive visions for the future of agriculture and food systems, unique starting points, and will therefore define their own transition pathways. This paper assesses how different policies (consumer oriented; producer oriented; market and food environment oriented; macro and trade oriented; and cross-cutting policies) can affect incentives for agroecology. It provides examples of policies and related actions taken by national, regional and city governments that intend to promote one or more agroecological principles. The assessment reveals that, until now, few countries have embarked on a broad set of reforms with sustained commitments. Many of these policies are new, weakly institutionalized and supported by limited budgets, making it difficult to analyze their actual effects. Because of this, there is very little research on how effective they have been in promoting agroecological transitions or the objectives that agroecology aims to achieve. Consequently, the paper’s main recommendation is for research to fill this gap so that future policy formulation and implementation can be better informed by experiences from different countries.